The complications of pain management and local anesthesia in endodontic treatments - A. Ghazinori (Tehran University of Medical Sciences, 1989)
Every individual may need endodontic treatments for more than once during lifetime. Therefore, a deep long anesthesia is desirable for the patients. In order to diagnose correctly and managing pain completely, modern developments should be concerned. By identifying the origin of pain and pain pathways, its management would be more effective. Nowadays, pain is considered   as a multifactorial phenomenon that can be influenced by many internal and external elements. In this article, the different theories on pain origin and pain pathway and finally on pain management methods are discussed and evaluated in detail.